Do social networks encourage risk-taking? Evidence from bank CEOs - Dbouk, Wassim; Fang, Yiwei; Liu, Liuling; Wang, Haizhi (Journal of Financial Stability, 2020)
This paper investigates the effects of CEO’s social network on bank risk-taking. We document a positive relation between bank CEO’s social connections and bank risks. To address the endogeneity concerns, we use deaths and retirements within networks to perform a difference-in-difference analysis, and find robust results. We also report that well-connected bank CEOs take more risk when more of their social ties are linked to informationally opaque firms and when the labor market offers fewer employment options. In addition, diversity of social ties (professional and educational) helps to mitigate the impact on risk. Finally, this study reveals an inefficient trade-off between bank risk and return, suggesting that executive social networks lead to excessive bank risk.